Development of interactive instructional materials based on the SAVI model using the ADDIE design in the introduction to computers course - Elfandry Bayunanda; Arief Rachman Andhika; Agustami Hamdan (Universitas PGRI Pontianak, 2025)
The rapid advancement of technology and the diversity of students’ learning styles necessitate innovative instructional materials that can provide interactive and adaptive learning experiences tailored to users’ needs. This study aims to develop interactive instructional materials based on the SAVI (Somatic, Auditory, Visual, Intellectual) learning model using the ADDIE framework for the Introduction to Computers course. The SAVI approach was selected to integrate physical activity, auditory input, visual representation, and intellectual reasoning within the learning process, enabling students to engage actively through holistic learning experiences. The development process involved two subject-matter experts, two media experts, and twenty undergraduate students as trial participants. Data were collected through validation questionnaires and user response surveys, which were analyzed using a Likert scale to assess the feasibility of the instructional materials. The results indicate that the materials achieved an average score of 4.6 for content quality, 4.4 for media design, and 4.3 for student responses, all of which fall into the “Highly Feasible” category. These findings demonstrate that integrating the SAVI model with multimodal learning theory can enhance student engagement and strengthen conceptual understanding through instructional media that are engaging, user-friendly, and aligned with the characteristics of contemporary digital learning in higher education.